2015
DOI: 10.1016/j.neuroscience.2015.07.026
|View full text |Cite
|
Sign up to set email alerts
|

Connexin36 expression in major centers of the auditory system in the CNS of mouse and rat: Evidence for neurons forming purely electrical synapses and morphologically mixed synapses

Abstract: Electrical synapses formed by gap junctions composed of connexin36 (Cx36) are widely distributed in the mammalian central nervous system (CNS). Here, we used immunofluorescence methods to document the expression of Cx36 in the cochlear nucleus and in various structures of the auditory pathway of rat and mouse. Labelling of Cx36 visualized exclusively as Cx36-puncta was densely distributed primarily on the somata and initial dendrites of neuronal populations in the ventral cochlear nucleus, and was abundant in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
37
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 85 publications
3
37
0
Order By: Relevance
“…As mentioned previously, the overlap of eighth nerve terminals with Cx35 puncta in dDO and dAO requires further study, but it is consistent with such observations on the goldfish lateral dendrite of the Mauthner neuron [Pereda et al, 2003] and in rodents, where unilateral labyrinthectomy results in almost complete homolateral depletion of Cx36 puncta in the ventral cochlear nucleus as well as in primary vestibular nuclei [Nagy et al, 2013;Rubio and Nagy, 2015]. This observation is also consistent with other morphological and/or physiological reports of mixed synapses between eighth nerve fibers and vestibular nuclei in agnathan and gnathostome fishes [Stefanelli and Caravita, 1970;Hinojosa, 1973;Rovainen, 1974;Korn et al, 1977], frogs [Precht et al, 1974;Babalian and Shapovalov, 1984], lizards [Richter Brain Behav Evol 2019;93:34-49 DOI: 10.115993:34-49 DOI: 10.…”
Section: Other Considerationssupporting
confidence: 83%
See 4 more Smart Citations
“…As mentioned previously, the overlap of eighth nerve terminals with Cx35 puncta in dDO and dAO requires further study, but it is consistent with such observations on the goldfish lateral dendrite of the Mauthner neuron [Pereda et al, 2003] and in rodents, where unilateral labyrinthectomy results in almost complete homolateral depletion of Cx36 puncta in the ventral cochlear nucleus as well as in primary vestibular nuclei [Nagy et al, 2013;Rubio and Nagy, 2015]. This observation is also consistent with other morphological and/or physiological reports of mixed synapses between eighth nerve fibers and vestibular nuclei in agnathan and gnathostome fishes [Stefanelli and Caravita, 1970;Hinojosa, 1973;Rovainen, 1974;Korn et al, 1977], frogs [Precht et al, 1974;Babalian and Shapovalov, 1984], lizards [Richter Brain Behav Evol 2019;93:34-49 DOI: 10.115993:34-49 DOI: 10.…”
Section: Other Considerationssupporting
confidence: 83%
“…Among primary vestibular nuclei, morphological studies similarly demonstrated that the eighth nerve forms mixed synapses with octaval nuclei in the lamprey [Stefanelli and Caravita, 1970;Rovainen, 1974], with the tangential nucleus (T) in the goldfish [Hinojosa, 1973], and with the lateral vestibular nucleus (or nucleus magnocellularis, MG) in the toadfish, where these synapses were physiologically confirmed [Korn et al, 1977]. The eighth nerve also forms mixed synapses with specific vestibular nuclei in species of amphibians [Precht et al, 1974;Babalian and Shapovalov, 1984], reptiles [Richter et al, 1975], birds [Hinojosa and Robertson, 1967;Wilson and Wylie, 1970], and mammals [Korn et al, 1973;Rubio and Nagy, 2015]. In the mammalian auditory system, two studies morphologically identified mixed synapses in the ventral cochlear nucleus [Sotello and Triller, 1982;Rubio and Nagy, 2015].…”
Section: Introductionmentioning
confidence: 95%
See 3 more Smart Citations